Pengaruh Return on Assets, Dividend Payout Ratio, Debt to Equity Ratio, dan Size terhadap Nilai Perusahaan (Studi Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2015 – 2019) - Kusuma Melati, Dinda; Prasetiono, Prasetiono (Faculty of Economics and Business Diponegoro University, 2021)
This study aims to examine the effect of Return on Assets (ROA), Dividend Payout Ratio (DPR), Debt to Equity Ratio (DER), and Firm Size on Firm Value proxied by Price to Book Value (PBV). The population in this study is manufacturing company in Indonesia which are listed on the Bursa Efek Indonesia (BEI) for the period 2015-2019. The number of samples in this study were 23 company, where the sample collection uses a purposive sampling method. The analysis technique used is multiple linear regression analysis and first performs the classic assumption test, the F statistical test, and the t statistical test. The results of hypothesis testing in this study indicate that ROA and DPR have significant positive effect on PBV, then DER have a negative and does not significant influence PBV, whereas Size have a positive and doesn’t significant effect on PBV. Based on the results of the study showed that the ROA variable had the greatest effect on PBV. The result of the R Square value is 0.211, so that 21,10% of the PBV variable can be explained by the ROA, DPR, DER, and Size, while the remaining 78,90% is explained by other variables outside in this study.